Designing for Digital Influence: The Impact of Gigi Susu's Facade on Social Media Branding - Canny Utami, I Gusti Ayu; Yogik Adnyana Putra, I Wayan; Ardiarani Utami, Ni Wayan (International Journal of Engineering, Science and Information Technology, 2025)
This research explores the impact of interior design, specifically the façade and interior features of Gigi Susu café, on its brand identity and success in social media branding. The study examines how the café's design elements—such as facade, signage, and natural aesthetics—contribute to its visibility on platforms like Instagram and shape customer perceptions of the brand. Using a mixed-methods approach, including content analysis of Instagram posts, customer surveys, and observational studies, the research investigates the role of "Instagrammable" design in fostering user-generated content (UGC) and customer engagement. Findings suggest that the café's visually distinctive and shareable design has enhanced brand recognition, positioning Gigi Susu as a prominent brand in Bali's competitive café market. The study concludes that facade design plays a crucial role in modern branding, emphasizing the need for businesses to consider both physical experiences and digital engagement in their design strategies. By aligning physical spaces with social media culture, companies can leverage design as a powerful digital influence and brand amplification tool.